PERSON-JOB FIT DENGAN WORK ENGAGEMENT PADA KARYAWAN MARKETING & SALES PT.Z - Ressy Mardiyanti (Fakultas Psikologi Universitas Wijaya Putra, 2023)
The aim of this research is to determine the relationship between Person Job Fit and work engagement in PT. Z. The compatibility between employees and the work they do is very important. With this compatibility, employees can carry out their work well, be immersed or have a strong attachment to their work, so that employees can stay in the company for a long time and can reduce the budget for the recruitment, selection and training process. The subject is an employee of the marketing & sales division of PT. Z, totaling 32 people and aged 19-45 years. This research uses quantitative methods, sampling using purposive sampling techniques, using measuring instruments with questionnaire models on the variables of person job fit and work engagement. The results of this research show a correlation value of 0.029 < 0.05, and if seen from the calculated correlation value it is 0.598 > 0.362, which means that there is a relationship between Person Job Fit and work engagement in employees of the Marketing & Sales Division of PT. Z. The higher a person's suitability for the job they are working on, the higher their work engagement. Matching between individuals and jobs at the start is very effective in reducing employee turnover, especially in marketing and sales functions.